2020
DOI: 10.1016/j.isci.2020.101810
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastin Modulates Anti-inflammatory Effects of MANF

Abstract: Summary Endoplasmic reticulum (ER) stress is known to induce pro-inflammatory response and ultimately leads to cell death. Mesencephalic astrocyte-derived neurotrophic factor (MANF) is an ER-localized protein whose expression and secretion is induced by ER stress and a crucial survival factor. However, the underlying mechanism of how MANF exerts its cytoprotective activity remains unclear due to the lack of knowledge of its receptor. Here we show that Neuroplastin (NPTN) is such a receptor for MANF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 49 publications
0
53
1
Order By: Relevance
“…Interaction with NPTN was needed for MANF-dependent cell survival and regulation of inflammation. As NPTN is an ER stress–inducible protein, it could account for cultured DA neurons becoming responsive to MANF on ER stress ( 42 ). However, more studies are needed to investigate where exactly do the mechanisms of intracellularly and extracellulary applied MANF converge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction with NPTN was needed for MANF-dependent cell survival and regulation of inflammation. As NPTN is an ER stress–inducible protein, it could account for cultured DA neurons becoming responsive to MANF on ER stress ( 42 ). However, more studies are needed to investigate where exactly do the mechanisms of intracellularly and extracellulary applied MANF converge.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very little is known about the MANF PPIs and their biological functions. We have recently shown neuroplastin (NPTN) to be a plasma membrane receptor for MANF ( 42 ), and another study suggested that the binding of MANF to the plasma membrane is modulated by KDEL endoplasmic reticulum protein retention receptors ( 43 ). In cellular models of multiple epiphyseal dysplasia MANF interacts with a V194D mutant of matrilin-3 that forms non-native disulfide bonds, suggesting that MANF functions as a part of ER stress response with other chaperones ( 36 ).…”
mentioning
confidence: 99%
“…in glia (Langnaese et al 1997). Neuroplastin has been shown to interact as a ligand with the fibroblast growth factor (FGF) receptor (Owczarek et al 2010), gamma-aminobutyric acid type A (GABAA) receptors (Sarto-Jackson et al 2012), S100A8/A9, basigin (Sakaguchi et al 2016;Sumardika et al 2019), mesencephalic astrocyte-derived neurotrophic factor (MANF) (Yagi et al 2020), tumor necrosis factor receptor-associated factor 6 (TRAF6) (Vemula et al 2020), and with itself undergoing homophilic binding (Langnaese et al 1997;Owczarek et al 2010). Furthermore, plasma membrane trafficking of monocarboxylic acid transporter 2 (MCT-2, SLC16A7) and XK-related protein 8 (Xkr8) may require neuroplastin as chaperone (Wilson et al 2013;Suzuki et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While MANF demonstrated potential to rescue cell bodies of dopamine neurons in the substantia nigra (SN) pars compacta (SNpc) in a 6-OHDA rat model, its protective effect on neuronal axons (the fibers of dopamine neurons in the striatum) was modest or absent (Voutilainen et al, 2009(Voutilainen et al, , 2011, making it a dubious NTF candidate for clinical trials in PD patients. However, the fact that MANF mitigates the inflammatory response and ER stress warrants further studies of neurorestorative potential of this NTF in other neurodegenerative diseases (Kovaleva et al, 2020;Yagi et al, 2020).…”
Section: Cerebral Dopamine Neurotrophic Factor (Cdnf)mentioning
confidence: 99%